HIGHER SCHOOL TRADITIONS: BORN TODAY AND IN DECADES LONG - Aleksey V. Pavlov; Natal'ya T. Eregina (Moscow Polytechnic University, 2016)
The article examines the traditions of education and upbringing of students at the Yaroslavl Medical Academy. Among the best university traditions there are those which have a long history and also newborn. It is shown how adherence to tradition becomes a real instrument for formation the spiritual culture of students, attaching them to the standards of the medical community, the best examples of Russian culture, historical memory.